The uronic acid content of coccolith-associated polysaccharides provides an insight into coccolithogenesis and past climate - Lee, R; Mavridou, D; Papadakos, G; McClelland, H; Rickaby, R (Nature Publishing Group, 2016)
Unicellular phytoplanktonic algae (coccolithophores) are amongst the most prolific producers of calcium carbonate on the planet, with a production of ~10^26 coccoliths/year. During their lith formation, coccolithophores mainly employ coccolith-associated polysaccharides (CAPs) for the regulation of crystal nucleation and growth. These macromolecules interact with the intracellular calcifying compartment (coccolith vesicle) through the charged carboxyl groups of their uronic acid residues. Here we report the isolation of CAPs from modern day coccolithophores and their prehistoric predecessors and we demonstrate that their uronic acid content (UAC) offers a species-specific signature. We also show that there is a correlation between the UAC of CAPs and the internal saturation state of the coccolith vesicle which, for most geologically abundant species, is inextricably linked to carbon availability. These findings suggest that the UAC of CAPs reports on the adaptation of coccolithogenesis to environmental changes and is a marker for the estimation of past pCO2 concentrations.